Research on the identification method of the pre-tightening state of the matching surface of the aero-engine disk-drum rotor. (June 2022) - Zou, Cunjian; Xia, Huateng; Chen, Kai; Zhai, Jingyu; Han, Qingkai
Highlights: The structural characteristics of the disk-drum rotor are summarized from the perspective of assembly. Three methods for identifying the preload state of the mating surface of an aero-engine disk-drum rotor are proposed. The refined finite element models are established to verify the correctness of the proposed methods. Abstract: The aero-engine rotor system is connected by one or more stages of mounting edges through bolts, and the pre-tightening state of the mating surface will directly affect the dynamic performance of the rotor and even the whole machine. However, there is little research on the identification method of the pre-tightening state of the mating surface of the disk-drum rotor with a multi-bolt flange connection. Therefore, based on the vibration theory, this paper analyzes the feasibility of the pre-tightening state identification method of the mating surface. Then, from the perspective of the assembly process and structural characteristics of the rotor system, this paper takes the high-pressure compressor disk-drum rotor, high-pressure turbine disk-drum rotor, and high-pressure rotor system as the research objects, respectively, and uses the finite element method and experimental method to analyze the influence of the pre-tightening state change of the mating surface on the rotor dynamic characteristics. Finally, according to the obtained regularity cognition, three pre-tightening state identification methods of multi-bolt connection mating surface are proposed: low-order vibration phase difference method, amplitude variation method of higher-order frequency response function (FRF), and axial tension-sensitive natural frequency offset method. The proposed methods can effectively identify the preload state of the mating surface of the disk-drum rotor in engineering due to improper assembly or harsh environment and provide a new research idea for the dynamic characteristic detection and assembly quality evaluation of aero-engine rotor.